HΛ3 and H‾Λ‾3 lifetime measurement in Pb–Pb collisions at sNN=5.02 TeV via two-body decay - Acharya, S.; Adamovã, D.; Adhya, S.P.; Adler, A.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; et al. (Elsevier, 2019)
An improved value for the lifetime of the (anti-)hypertriton has been obtained using the data sample of Pb–Pb collisions at √sNN = 5.02 TeV collected by the ALICE experiment at the LHC. The (anti-)hypertriton has been reconstructed via its charged two-body mesonic decay channel and the lifetime has been determined from an exponential fit to the dN/d(ct) spectrum. The measured value, τ = 242+34 −38 (stat.) ± 17 (syst.) ps, is compatible with representative theoretical predictions, thus contributing to the solution of the longstanding hypertriton lifetime puzzle
Keywords: Hypertriton lifetime; Pb–Pb collisions; https://purl.org/pe-repo/ocde/ford#1.03.04